The influence of genetic factors on personality and coping with stress among healthy late reproductive age women - Jurczak A (Dove Medical Press, 2019)
Anna Jurczak,1 Małgorzata Szkup,2 Krzysztof Safranow,3 Agnieszka Samochowiec,4 Sylwia Wieder-Huszla,1 Joanna Owsianowska,1 Elżbieta Grochans21Department of Clinical Nursing, Pomeranian Medical University in Szczecin, Szczecin, Poland; 2Department of Nursing, Pomeranian Medical University in Szczecin, Szczecin, Poland; 3Department of Biochemistry, Pomeranian Medical University in Szczecin, Szczecin, Poland; 4Department of Clinical Psychology, Institute of Psychology, University of Szczecin, Szczecin, PolandBackground: Psychological stress is a factor which predisposes people to many somatic and mental disorders. Women are at a significantly higher risk of stress than men, and their reactions to stress are stronger. Personality traits are thought to play a special role in the psychology of stress and may be crucial for the choice of a stress-coping strategy. Considering that stress is so common in everyday life, an attempt to understand how stress-coping styles are related to personality and genetic factors acquires special significance.Purpose: The aim of this study was to analyze stress-coping styles and personality traits in healthy late reproductive age women with regard to genetic factors.Patients and methods: The study involved 345 healthy late reproductive age women from northwest Poland, whose mean age was 42.3±4.5 years. The study was conducted using The Coping Inventory for Stressful Situations, The Neuroticism-Extraversion-Openness Five--Factor Inventory, and genetic testing.Results: There were neither statistically significant relationships between personality traits and the genotype distribution of the 30-bp VNTR polymorphism in the MAO-A promoter region, nor between stress-coping styles and the genotype distribution of the 30-bp VNTR polymorphism in the MAO-A promoter region.Conclusion: Based on the results, all personality traits statistically significantly correlated with the choice of task-oriented coping and emotion-oriented coping. Some of personality traits are genetically determined. The choice of a stress-coping style was significantly related to personality traits. A direct influence of genetic factors on the choice of a stress-coping style was not confirmed in our study.Keywords: stress, personality, polymorphism, women